Thyroid gland functions are affected in obsessive compulsive disorder - Mermi, Osman; Atmaca, Murad (Cumhuriyet Univ Tip Fak Psikiyatri Anabilim Dali, 2016)
Objective: In the present study, it was aimed to examine thyroid functions in a group of patients with obsessive compulsive disorder (OCD) who had not any comorbid conditions. Methods: Our present study included forty patients diagnosed with OCD and forty healthy controls. The subjects were selected by the chart reviews among the patients with OCD who had applied to the Firat University School of Medicine Department of Psychiatry, as inpatients or outpatients and had met the criteria of the present investigation. Thyroid hormone values had been obtained by using an auto analyzer. Results: Independent t test revealed that there were no statistically significant differences thyroid stimulating hormone (TSH) values between the patients with OCD and healthy control subjects whereas there were statistically significant reduced levels of free triiodothyronine (FT3) and free thyroxine (FT4) hormones in the patient group compared to those of healthy ones. Conclusion: Consequently, altered levels of thyroid hormones may be associated with pathophysiology or at least maintenance of OCD.
Obsesif kompulsif bozuklukta tiroid işlevleri etkilenmektedir
Keywords: OCD; TSH; thyroid hormones